LEARNING GUIDANCE AS AN EFFORT TO CREATE STUDENT LEARNING INDEPENDENCE - Annisa Puji Rahayu; Novi Andriani (khidmatan, 2022)
With independent learning, a student can solve problems related to his studies without depending on the teacher or classmates. Then is the character of someone who believes more in his abilities and tries to be free from dependence on others in adjusting to his problems, based on a creative and innovative character. This community service uses the Participatory Action Research (PAR) method by directly extracting various information, then taking action as a solution to the problems identified by participating in developing the design and implementation of actions based on research results. The tutoring program aims to help increase students' independence in learning. With the tutoring program, the students became more enthusiastic about learning. Increased enthusiasm for learning can mean that students have increased learning independence.